Amity University Noida B.Tech Admissions 2025
ApplyAmong Top 30 National Universities for Engineering (NIRF 2024) | 30+ Specializations
Homogeneous Differential Equation is considered one the most difficult concept.
38 Questions around this concept.
Which of the following is not a Homogeneous D.E?
Which of the following is reducible to homogeneous equation
The solution of the differential equation $\left(x^2+y^2\right) d x-5 x y d y=0, y(1)=0$, is :
New: JEE Main 2025 Official Answer Key OUT; Download Now
JEE Main 2025: Rank Predictor | College Predictor | Marks vs Rank vs Percentile
JEE Main 2025 Memory Based Question: Jan 22, 23, 24, 28 & 29 (Shift 1 & 2)
JEE Main 2025: High Scoring Topics | Sample Papers | Mock Tests | PYQs
If $y=y(x)$ and $\frac{2+\sin x}{y+1} \frac{d y}{d x}=-\cos x, y(0)=1$, then $y\left(\frac{\pi}{2}\right)$is equal to
A function $f(x, y)$ is said to be a homogeneous function of degree $n$ if it satisfies the property
$
f(\lambda x, \lambda y)=\lambda^n f(x, y)
$
Consider the following examples
1. $f(x, y)=x^3-4 x y^2$
2. $f(x, y)=x-3 y$
3. $f(x, y)=\tan \frac{x}{y}$
in the above examples if we replace x and y with $\lambda \mathrm{x}$ and $\lambda \mathrm{y}$, where $\lambda$ is non - zero, we get
1. $\mathrm{f}(\lambda \mathrm{x}, \lambda \mathrm{y})=(\lambda \mathrm{x})^3-4(\lambda \mathrm{x})(\lambda \mathrm{y})^2=\lambda^3\left(\mathrm{x}^3-4 \mathrm{xy}{ }^2\right)=\lambda^3 \mathrm{f}(\mathrm{x}, \mathrm{y})$
2. $\mathrm{f}(\lambda \mathrm{x}, \lambda \mathrm{y})=\lambda \mathrm{x}-3(\lambda \mathrm{y})=\lambda(\mathrm{x}-3 \mathrm{y})=\lambda \mathrm{f}(\mathrm{x}, \mathrm{y})$
3. $\mathrm{f}(\lambda \mathrm{x}, \lambda \mathrm{y})=\tan \frac{\lambda \mathrm{x}}{\lambda \mathrm{y}}=\tan \frac{\mathrm{x}}{\mathrm{y}}=\lambda^0 \mathrm{f}(\mathrm{x}, \mathrm{y})$
Now, if the function is given as
4. $\mathrm{f}(\mathrm{x}, \mathrm{y})=\sin \mathrm{x}+\cos \mathrm{y}$, then $\mathrm{f}(\lambda \mathrm{x}, \lambda \mathrm{y}) \neq \lambda^{\mathrm{n}} \mathrm{f}(\mathrm{x}, \mathrm{y})$
Observe that it is possible to write examples 1,2 and 3 in the form of $f(\lambda x, \lambda y)=\lambda^n f(x, y)$.
But example 4 can't be written in this form. $^2$.
Here, examples 1, 2, and 3 are homogeneous equations of degree 3,1 and 0 respectively and example 4 is not a homogeneous function.
We can define homogeneous differential equation as follows:
Any DE of the form $M(x, y) d x+N(x, y) d y=0$ or $\frac{d y}{d x}=-\frac{M(x, y)}{N(x, y)}$ is called homogeneous if $M(x, y)$ and $N(x, y)$ are homogeneous functions of the same degree.
Since, $M(x, y)$ and $N(x, y)$ are both homogeneous function of degree $n$, then DE can be reduced to a function of $\mathrm{y} / \mathrm{x}$
$
\frac{d y}{d x}=-\frac{M(x, y)}{N(x, y)}=\phi\left(\frac{y}{x}\right)
$
This equation can be solved by the substitution $\mathrm{y}=\mathrm{vx}$.
$
\Rightarrow \quad \begin{aligned}
\mathrm{y} & =\mathrm{vx} \\
\Rightarrow \quad \frac{\mathrm{dy}}{\mathrm{dx}} & =\mathrm{v}+\mathrm{x} \frac{\mathrm{dv}}{\mathrm{dx}}
\end{aligned}
$
Thus, $\frac{d y}{d x}=\phi\left(\frac{y}{x}\right)$ transforms to
$
\begin{aligned}
\mathrm{v}+\mathrm{x} \frac{\mathrm{dv}}{\mathrm{dx}} & =\phi(\mathrm{v}) \\
\Rightarrow \quad \frac{d v}{\phi(v)-v} & =\frac{d x}{x}
\end{aligned}
$
The variables have now been separated and the solution is
$
\int \frac{\mathrm{dv}}{\phi(\mathrm{v})-\mathrm{v}}=\ln \mathrm{x}+\mathrm{c}
$
After the integration v should be replaced by $y / x$ to get the required solution.
If the differential equation is of the form
$
\frac{d y}{d x}=\frac{a x+b y+c}{d x+e y+f}
$
It can be reduced to a homogeneous differential equation as follows:
Put $x=X+h, y=Y+k$
where X and Y are new variables and h and k are constants yet to be chosen
From (2)
$
d x=d X, d y=d Y
$
Equation (1), thus reduces to
$
\frac{d Y}{d X}=\frac{a(X+h)+b(Y+k)+c}{d(X+h)+e(Y+k)+f}=\frac{a X+b Y+(a h+b k+c)}{d X+e Y+(d h+e k+f)}
$
In order to have equation (3) as a homogeneous differential equation, choose h and k such that the following equations are satisfied :
$
\left.\begin{array}{rl}
a h+b k+c & =0 \\
d h+e k+f & =0
\end{array}\right\}
$
Now, (3) becomes
$
\frac{d Y}{d X}=\frac{a X+b Y}{d X+e Y}
$
which is a homogeneous differential equation and can be solved by putting $\mathrm{Y}=\mathrm{vX}$.
Note:
If $\mathrm{d} / \mathrm{a}=\mathrm{e} / \mathrm{b}$ (=t say), the above method does not apply.
In such cases, Equation (1) becomes
$
\frac{d y}{d x}=\frac{a x+b y+c}{t(a x+b y)+f}
$
which can be solved by putting $a x+b y=v$
Separate the variables and integrate them to get the required solution.
"Stay in the loop. Receive exam news, study resources, and expert advice!"